Factors associated with uptake of measles, mumps, and rubella vaccine (MMR) and use of single antigen vaccines in a contemporary UK cohort: prospective cohort study. Issue 7647 (28th February 2008) - Pearce, Anna; Law, Catherine; Elliman, David; Cole, Tim J; Bedford, Helen
Abstract : Objectives To estimate uptake of the combined measles, mumps, and rubella vaccine (MMR) and single antigen vaccines and explore factors associated with uptake and reasons for not using MMR. Design Nationally representative cohort study. Setting Children born in the UK, 2000-2. Participants 14 578 children for whom data on immunisation were available. Main outcome measures Immunisation status at 3 years defined as "immunised with MMR, " "immunised with at least one single antigen vaccine, " and "unimmunised." Results 88.6% (13 013) were immunised with MMR and 5.2% (634) had received at least one single antigen vaccine. Children were more likely to be unimmunised if they lived in a household with other children (risk ratio 1.74, 95% confidence interval 1.35 to 2.25, for those living with three or more) or a lone parent (1.31, 1.07 to 1.60) or if their mother was under 20 (1.41, 1.08 to 1.85) or over 34 at cohort child's birth (reaching 2.34, 1.20 to 3.23, for ≥40), more highly educated (1.41, 1.05 to 1.89, for a degree), not employed (1.43, 1.12 to 1.82), or self employed (1.71, 1.18 to 2.47). Use of single vaccines increased with household income (reaching 2.98, 2.05 to 4.32, for incomes of ≥£52 000 (€69 750, 102 190)), maternal age (reaching 3.04, 2.05 to 4.50, for ≥40), and education (reaching 3.15, 1.78 to 5.58, for a degree). Children were less likely to have received single vaccines if they lived with other children (reaching 0.14, 0.07 to 0.29, for three or more), had mothers who were Indian (0.50, 0.25 to 0.99), Pakistani or Bangladeshi (0.13, 0.04 to 0.39), or black (0.31, 0.14 to 0.64), or aged under 25 (reaching 0.14, 0.05 to 0.36, for 14-19). Nearly three quarters (74.4%, 1110) of parents who did not immunise with MMR made a "conscious decision" not to immunise. Conclusions Although MMR uptake in this cohort is high, a substantial proportion of children remain susceptible to avoidable infection, largely because parents consciously decide not to immunise. Social differentials in uptake could be used to inform targeted interventions to promote uptake.